The Land 'Wars' in Twenty-First Century Patagonia. Issue 1 (2nd January 2019) - Aliaga, Cristian
Abstract : A front line report from the struggles between the First Peoples of the Southern Cone and the new extractivist paradigm. A prominent Patagonian journalist and poet reports on privatisation, state repression, and the offshoring of territorial and subsoil rights, as well as ongoing legal cases including the death of Santiago Maldonado and the detention of Facundo Jones Huala. Legacies of the "Conquest of the Desert" and a future Argentina without the far south.